2016
DOI: 10.1007/s00224-016-9687-z
|View full text |Cite
|
Sign up to set email alerts
|

Stable Marriage with General Preferences

Abstract: Abstract. We propose a generalization of the classical stable marriage problem. In our model, the preferences on one side of the partition are given in terms of arbitrary binary relations, which need not be transitive nor acyclic. This generalization is practically well-motivated, and as we show, encompasses the well studied hard variant of stable marriage where preferences are allowed to have ties and to be incomplete. As a result, we prove that deciding the existence of a stable matching in our model is NP-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 24 publications
0
27
0
Order By: Relevance
“…Some notable mentions out of those lists are Shapely and Shubik [28], X. Deng et al [12], Granot et al [16], X. Deng and Q. Fang [11], Chalkiadakis et al [8], etc. Farczadi et al [14] extended the results of the Kleinberg-Tardos model for networks with agents with general capacities. Hajiaghayi et al [18] also did the work in that line.…”
Section: Previous Workmentioning
confidence: 98%
See 1 more Smart Citation
“…Some notable mentions out of those lists are Shapely and Shubik [28], X. Deng et al [12], Granot et al [16], X. Deng and Q. Fang [11], Chalkiadakis et al [8], etc. Farczadi et al [14] extended the results of the Kleinberg-Tardos model for networks with agents with general capacities. Hajiaghayi et al [18] also did the work in that line.…”
Section: Previous Workmentioning
confidence: 98%
“…In our work we build on top of the study of Kleinberg and Tardos [21], Bateni et al [2] and Farczadi et al [14]. The common thread between their work and ours is the study of stability over a network bargaining game.…”
Section: Our Contributionmentioning
confidence: 99%
“…They also considered the case of certain, but cyclic preferences and showed that deciding whether a weakly stable matching exists is NP-complete if both sides can have cycles in their preferences. Strongly and super stable matchings were discussed by Farczadi et al [11]. Throughout their paper they assumed that one side has strict preferences, and proved that finding a strongly or a super stable matching (or proving that none exists) can be done in polynomial time if the other side has cyclic lists, where cycles of length at least 3 are permitted to occur, but the problems become NP-complete as soon as cycles of length 2 are also allowed.…”
Section: Related Workmentioning
confidence: 99%
“…While it would lead to an equally correct model, we chose incomparability over being equally good consciously. Some early papers [19,20] do not distinguish between two agents being incomparable and equally good, while some others in the more recent literature [3,11] motivate strong and super-stability with uncertain information. Our definition fits the more recent framework.…”
Section: Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation